2009
DOI: 10.4049/jimmunol.0900714
|View full text |Cite
|
Sign up to set email alerts
|

Functionally Mature CD4 and CD8 TCRαβ Cells Are Generated in OP9-DL1 Cultures from Human CD34+ Hematopoietic Cells

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
2
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 49 publications
(58 citation statements)
references
References 50 publications
3
52
2
1
Order By: Relevance
“…Although two groups have reported the generation of mature single-positive T cells in OP9/DLL co-cultures [3,8], others failed [7]. Furthermore, questions remain about the functionality of these in vitro-matured T cells regarding their MHC-restriction and some phenotypic abnormalities [8]. In accordance with our data, Meek et al recently reported the same maturation arrest at the T/NK-progenitor cell level using a DLL-4 over-expressing stroma cell line [7].…”
Section: Cd7mentioning
confidence: 99%
“…Although two groups have reported the generation of mature single-positive T cells in OP9/DLL co-cultures [3,8], others failed [7]. Furthermore, questions remain about the functionality of these in vitro-matured T cells regarding their MHC-restriction and some phenotypic abnormalities [8]. In accordance with our data, Meek et al recently reported the same maturation arrest at the T/NK-progenitor cell level using a DLL-4 over-expressing stroma cell line [7].…”
Section: Cd7mentioning
confidence: 99%
“…RNA extraction, cDNA synthesis and RT-PCR were performed as described preciously. 18 The Figure 1 Phenotype of TCRgd þ thymocytes. Fresh postnatal thymocytes were labeled and analyzed by 7-color flow cytometry.…”
Section: Rna Isolation and Real-time (Rt)-pcrmentioning
confidence: 99%
“…18 An overview of the antibodies that were used can be found in Supplementary Materials. Flow cytometric analysis was performed using a LSR II Cytometer (BD Biosciences).…”
Section: Flow Cytometrymentioning
confidence: 99%
See 2 more Smart Citations